Investigation of inter‐relationship between tensile behavior and photocatalytic activity of an acrylic‐based composite upon UVA exposure. Issue 6 (30th September 2016) - Dianatdar, Afshin; Jamshidi, Masoud
ABSTRACT: The aim of this work is to produce a photocatalytic pseudo‐paint for benzene removal from air and find the role of TiO2 nanoparticles, TiO2 pigment, and CaCO3 extender on photocatalytic performance of this paint along with their role on stress–strain behavior after ultraviolet (UV) exposure. For this purpose, TiO2 nanoparticles were dispersed into an indoor paint resin (i.e., copolymer acrylic–styrene). The impact of main components of the paint on photocatalytic oxidation (PCO) rate of benzene was studied. It was found that dispersion of nanoparticles had the most dramatic effect on photo activity of nanocomposite. TiO2 pigment generally increased PCO rate and also made the paint more stable under tensile stress. CaCO3 may increase and/or decrease PCO of benzene, whether there is pigment in the formulation or not. However, it does not generally contribute to making the formulation resistant to UV exposure. Nanoparticles bring PCO and mechanical strength into the paint, but fail to strengthen the composite against UV deterioration. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44447. Abstract :